LEGAL PROTECTION FOR CHILD VICTIMS INVOLVED BY DOMESTIC VIOLENCE IN THE RESTORATIVE JUSTICE IMPLEMENTATION (CASE STUDY AT PUBLIC PROSECUTION SERVICE OF LABUHAN BATU DISTRICT IN 2023) - Elisa Yuliana Lumban Batu; Mahmud Mulyadi; Vita Cita Emia Tarigan (CV Rewang Rencang, 2024)
Cases of domestic violence that occur in Indonesia not only result in women as victims, but can also occur in children. The problem formulation in this thesis is: What is the role of the Labuhan Batu District Prosecutor's Office in providing legal protection towards child victims of domestic violence through a Restorative Justice approach; What are the obstacles for the Labuhan Batu District Prosecutor's Office in providing legal protection for child victims of domestic violence through a Restorative Justice approach? The research method used in this journal is the sociological juridical research method. The results of this research can be concluded that restorative justice can be implemented with the following requirements: the threat of a sentence of no more than 5 (five) years, the perpetrator is not a recidivist, there is the victim's consent or desire to make peace, there is good faith from the suspect to fulfill the obligations agreed between the victim and the suspect , and there must be an agreement between the victim, the suspect and other parties